17‐3: Simultaneous Optimization of Color Contrast and Color Rendering Index for Surgical Lighting. Issue 1 (May 2016) - Wang, Huihui; Cuijpers, Raymond H.; Vogels, Ingrid M. L. C.; Heynderickx, Ingrid; Luo, Ming Ronnier; Zheng, Zhenrong
Abstract : A method was explored to optimize the illumination spectrum for surgical lighting. The method simultaneously enhances the color contrast of biological tissue and the color rendering index (CRI) of the light source. Compared to conventional surgical lighting (i.e. based on halogen light sources), the optimized illumination has better color contrast and sufficiently high color rendering, i.e. both CIE Ra and R9 values are above 85.